2004
DOI: 10.1007/s00063-004-1105-7
|View full text |Cite
|
Sign up to set email alerts
|

Reizdarmsyndrom: Koloskopie schmerzhaft und schwierig?

Abstract: Regarding perception of procedure-related pain and technical problems in colonoscopy, patients with IBS do not show significant differences compared to patients without IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…One study of children undergoing endoscopy under conscious sedation showed that those with greater anxiety exhibited more procedure related distress (23). However, studies comparing pain symptoms during colonoscopy between adults with IBS and those with other conditions have been contradictory (22,24).…”
Section: Introductionmentioning
confidence: 99%
“…One study of children undergoing endoscopy under conscious sedation showed that those with greater anxiety exhibited more procedure related distress (23). However, studies comparing pain symptoms during colonoscopy between adults with IBS and those with other conditions have been contradictory (22,24).…”
Section: Introductionmentioning
confidence: 99%